2017
DOI: 10.1292/jvms.16-0562
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of canine gallbladder contents in biliary sludge and gallbladder mucoceles

Abstract: The pathophysiology of canine gallbladder diseases, including biliary sludge, gallbladder mucoceles and gallstones, is poorly understood. This study aimed to evaluate the component of gallbladder contents and bacterial infection of the gallbladder in order to elucidate the pathophysiology of biliary sludge and gallbladder mucoceles. A total of 43 samples of canine gallbladder contents (biliary sludge, 21 and gallbladder mucoceles, 22) were subjected to component analysis by infrared spectroscopy, and the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 26 publications
2
30
1
1
Order By: Relevance
“…The reason for perioperative death following cholecystectomy for treatment of GBM is not well understood. Although concurrent bacterial infection has not been correlated with perioperative mortality (Besso et al 2000, Pike et al 2004, Worley et al 2004, Aguirre et al 2007, Crews et al 2009, Uno et al 2009, Malek et al 2013, the rate of bacterial infection has been variably described (Pike et al 2004, Worley et al 2004, Aguirre et al 2007, Crews et al 2009, Uno et al 2009, Malek et al 2013, Mizutani et al 2017, which may limit the ability to make this correlation. In our two cases of perioperative death with cholecystitis and bacteria detected by FISH, death due to complications of cholecystitis (such as haemodynamic instability) (Amsellem et al 2006, Papazoglou et al 2008) and/or translocation of bacteria from the biliary system and resulting septicaemia could be considered as possible causes.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for perioperative death following cholecystectomy for treatment of GBM is not well understood. Although concurrent bacterial infection has not been correlated with perioperative mortality (Besso et al 2000, Pike et al 2004, Worley et al 2004, Aguirre et al 2007, Crews et al 2009, Uno et al 2009, Malek et al 2013, the rate of bacterial infection has been variably described (Pike et al 2004, Worley et al 2004, Aguirre et al 2007, Crews et al 2009, Uno et al 2009, Malek et al 2013, Mizutani et al 2017, which may limit the ability to make this correlation. In our two cases of perioperative death with cholecystitis and bacteria detected by FISH, death due to complications of cholecystitis (such as haemodynamic instability) (Amsellem et al 2006, Papazoglou et al 2008) and/or translocation of bacteria from the biliary system and resulting septicaemia could be considered as possible causes.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (2017) have observed an association between ACTH-dependent HAC and cholestatic disease, and that patients with such comorbidity need higher doses of trilostane. A recent study has also shown it is possible that gallbladder mucoceles and biliary sludge have the same physiopathology, thus representing a continuous disease, with biliary sludge being considered the stage before gallbladder mucoceles appearance (Kutsunai et al 2014, Mizutani et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research investigating the administration of various drugs and the role of genetic mutations similarly have been unable to define a specific etiology for GBM formation. Compelling evidence supports the theory that gallbladder dysmotility, decreased bile flow or stasis, and altered bile composition contribute to the formation of mucoceles but whether these abnormalities represent discrete diseases or secondary manifestations of other systemic diseases is unknown …”
Section: Introductionmentioning
confidence: 99%